Development and validation of a web application for physiotherapy management in the trauma-orthopedics area (Research, Society and Development, 2023)
Due to advances in technology in all areas, there was the introduction of technological resources as facilitators in the health area. Therefore, this study aimed to develop and validate a web application for physiotherapy management in the area of ​​traumato-orthopedics. This is a methodological study of the production and validation of healthcare and educational technology, carried out between October 2021 and November 2022, at the University of the State of Pará, through 4 phases: situational diagnosis, literature review, formulation and assembly of the web application and its validation. The development of the app followed with two technical stages, the front-end and the back-end. The content validation stage with the expert judges was performed using a validated instrument, which is divided into two parts, the first with information about the expert judges and the second with 22 questions regarding the technology presented. Nine Physiotherapists participated in the research, with an average training time of 21.00±6.38 years. In the first and only round of validation, a Content Validity Index (CVI) of 0.96 was observed for the objectives block, 0.99 for the structure and presentation block, and 0.96 for the relevance block, with an overall CVI of 0.97, which is considered statistically valid. It is concluded that the web application proved to be a valid and adequate device to be made available to physiotherapists working in trauma and orthopedics, and can bring benefits in several aspects.